Contribution of fly ash to mortar strength development under steam and internal curing - Ryo Insako; Yuki Miyoshi; Phat Tan Huynh; Yuko Ogawa; Kenji Kawai (Acta Polytechnica CTU Proceedings, 2022)
The purpose of this study is to quantitatively evaluate the effects of steam curing and internal curing on contribution of fly ash to strength development of mortar by using cementing efficiency factor (k-value) that represents strength development performance as a binder of fly ash. In addition, the pozzolanic reaction of fly ash was evaluated from the viewpoint of calcium hydroxide consumption by using thermogravimetry and differential thermal analysis as well as the degree of fly ash reaction by using selective dissolution method. The result indicated that steam curing improved early compressive strength and internal curing improved compressive strength and k-value at all ages. Also, a linearrelationship between the degree of fly ash reaction and the k-value was shown regardless of the age and the replacement ratio of fly ash.